Investigation of Retinal Metabolic Function in Type 1 Diabetic Akita Mice - Shosha, Esraa; Qin, Luke; Lemtalsi, Tahira; Zaidi, Syed A. H.; Rojas, Modesto; Xu, Zhimin; Caldwell, Robert William; Caldwell, Ruth B.; Fouda, Abdelrahman Y. (Frontiers in Cardiovascular Medicine, 2022)
Diabetic retinopathy (DR) is the leading cause of vision loss in working age adults. Understanding the retinal metabolic response to circulating high glucose levels in diabetic patients is critical for development of new therapeutics to treat DR. Measuring retinal metabolic function using the Seahorse analyzer is a promising technique to investigate the effect of hyperglycemia on retinal glycolysis and mitochondrial respiration. Here, we analyzed the retinal metabolic function in young and old diabetic and control mice. We also compared the expression of key glycolytic enzymes between the two groups. The Seahorse XF analyzer was used to measure the metabolic function of retina explants from young and old type 1 diabetic Akita (Ins2Akita/+) mice and their control littermates. Rate-limiting glycolytic enzymes were analyzed in retina lysates from the two age groups by Western blotting. Retinas from young adult Akita mice showed a decreased glycolytic response as compared to control littermates. However, this was not observed in the older mice. Western blotting analysis showed decreased expression of the glycolytic enzyme PFKFB3 in the young Akita mice retinas. Measurement of the oxygen consumption rate showed no difference in retinal mitochondrial respiration between Akita and WT littermates under normal glucose conditions ex-vivo despite evident mitochondrial fragmentation as examined by electron microscopy. However, Akita mice retinas showed decreased mitochondrial respiration under glucose-free conditions. In conclusion, diabetic retinas display a decreased glycolytic response during the early course of diabetes which is accompanied by a reduction in PFKFB3. Diabetic retinas exhibit decreased mitochondrial respiration under glucose deprivation.